2021
DOI: 10.3855/jidc.13815
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group influence COVID-19 infection: a meta-analysis

Abstract: Introduction: Previous studies have linked the relationship between ABO blood group and COVID-19 infection. However, existing evidence is preliminary and controversial. This meta-analysis sought to identify studies that describe COVID-19 and ABO blood group. Methodology: A literature search was conducted from PubMed, Web of Science, MedRxiv, BioRxiv and Google Scholar databases. Members of cases and controls were extracted from collected studies. Pooled Odds ratio (OR) and 95% confidence interval (95%CI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The most common viral marker was HBsAg (0.38%), followed by anti-HCV (0.13%), syphilis (0.02%), and anti-HIV (0.006%), and male donors were more infected than female donors [ 37 ]. One recent example was the association of ABO groups with COVID-19, suggesting that those with group A and AB are more prone to the infection, while those with group O are less susceptible [ 38 ]. This study showed that donors with the O blood group, particularly those with O RhD +ve blood group, were more at risk of developing TTIs, whereas donors with the AB blood group, the AB RhD −ve blood group, in particular, were at the lowest risk of developing TTIs.…”
Section: Discussionmentioning
confidence: 99%
“…The most common viral marker was HBsAg (0.38%), followed by anti-HCV (0.13%), syphilis (0.02%), and anti-HIV (0.006%), and male donors were more infected than female donors [ 37 ]. One recent example was the association of ABO groups with COVID-19, suggesting that those with group A and AB are more prone to the infection, while those with group O are less susceptible [ 38 ]. This study showed that donors with the O blood group, particularly those with O RhD +ve blood group, were more at risk of developing TTIs, whereas donors with the AB blood group, the AB RhD −ve blood group, in particular, were at the lowest risk of developing TTIs.…”
Section: Discussionmentioning
confidence: 99%
“…The RBC surface of blood group A contains antigen A and the serum/plasma contains anti-B antibodies. Blood group A has been linked to a higher risk of HIV [ 10 , 11 ], HBV [ 11 ], HCV [ 12 ], COVID-19 [ 13 , 14 ], malaria, smallpox, enterotoxoid-mediated cholera, glue ear, capsular glaucoma, and heart disease, as well as a number of cancers, including gastric, breast, ovarian, cervical, leukemia (ALL), and leukemia of the pancreas[ 8 ], HCV related hepatocellular carcinoma (HCC)[ 15 ] Non-secretors of blood group A are linked to non-insulin-dependent diabetes, ankylosing spondylitis, Graves' disease, and coeliac disease [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study result shows that blood group B had a significantly higher frequency of 39.92% for blood issues (p = 0.0000) and 39.34% for platelet (RDP) issues (p = 0.0000) and a lower frequency of 37.32% for FFP issues (p = 0.00024), compared to the frequency of blood donors at 37.53%.The RBC surface of blood group B contains antigen B and the serum has anti-A antibodies. Blood group B has an association with a higher risk of HCV[ 12 ],Transfusion transmitted infections (TTIs) [ 1 12, 16 ], COVID-19 [ 14 ], HCV related HCC [ 15 ], Malaria, Typhoid, Filariasis, Enterotoxoid-Mediated Cholera, Coeliac Disease, Ankylosing Spondylitis Graves disease and non-insulin dependent diabetes are associated with B non-secretors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“… 43–45 One meta-analysis showed that people with blood group A are more vulnerable to COVID-19 infection and blood group AB is less susceptible to getting infected with SARS-CoV-2, 43 while another meta-analysis observed that both blood groups A and AB are linked to COVID-19 infection and individuals with blood group O are relatively less vulnerable. 44 Therefore, the association between blood group and COVID-19 positivity is still enigmatic.…”
Section: Discussionmentioning
confidence: 99%